Efficacy of Gasserian Ganglion High-Voltage, Long-Duration Pulsed Radiofrequency Combined With Block on Acute/Subacute Zoster-Related Trigeminal Neuralgia - Yinghao Song; Ziheng Yu; Jingjing Guan; Haisheng Wu; Qiaoling Liu; Min Yuan; Xinzhi Cheng; Bingyu Ling (Pain Research and Management)
Conclusions: Gasserian ganglion HL-PRF combined with block can be an effective and safe technique to relieve the pain of acute/subacute zoster-related trigeminal neuralgia and prevent the incidence of TPHN.